Strengthening Computational Thinking Skills through Blended Learning, Digital Literacy and Learning Environment: The Role of Learning Motivation as a Mediating Variable - Niny Makaliwe; Listriyanti Palangda; Jety Lempas; Ilham Abu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the effects of blended learning, digital literacy, and the learning environment on students' computational thinking skills, with learning motivation as a mediating variable. A quantitative approach was employed, employing Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The study involved 215 high school students selected through purposive sampling, specifically students with experience in digital and blended learning environments. Data were collected using a questionnaire covering indicators of blended learning, digital literacy, learning environment, learning motivation, and computational thinking skills. Data analysis included external model testing for validity and reliability using Confirmatory Factor Analysis (CFA) and model testing using path coefficients, R-squared, and mediation analysis. The findings indicated that blended learning significantly influenced computational thinking skills (β = 0.059; p = 0.009) and learning motivation (β = 0.167; p = 0.001). The learning environment also showed a significant influence on computational thinking (β = 0.199; p = 0.008) and learning motivation (β = 0.471; p < 0.001). Learning motivation had the strongest direct influence on computational thinking (β = 0.509; p < 0.001). The SEM-PLS model showed adequate predictive power, with R-square values of 0.541 for computational thinking and 0.464 for learning motivation. Mediation analysis showed that learning motivation significantly mediated the relationship between blended learning and computational thinking (β = 0.085; p < 0.001), as well as the learning environment and computational thinking (β = 0.240; p < 0.001). However, the mediation effect between digital literacy and computational thinking was not significant (β = 0.023; p = 0.752), indicating that digital literacy directly influences computational thinking through students' cognitive and information processing abilities. This finding highlights the importance of integrating technology-based learning, a supportive learning environment, and motivational factors to strengthen computational thinking skills.